A Study on the Impact of Financial Skill on Entrepreneurial Venture Failure - Kamle, Deepali Vijay (SFIMAR Research Review, 2017)
New venture creation is very important for the economic development of the country. Entrepreneurship is the driving force behind job creation, innovation, economic growth and healthy sustainable start-ups. The start-up founders with their diverse and versatile behaviour helps in innovation, combining new resources. Further, when it comes to youth, entrepreneurship represents an increasingly important source of employment. Starting a new venture can be very difficult for the young people. The financial, social, and knowledge capital stocks of young entrepreneurs are often deficient, and these founders often lack the ability to obtain these resources externally. Scholars have long noted that young firms have higher failure rates than the established firms. On an average 50 per cent of the start-up ventures die within a span of two years or earlier, 10 per cent in ten years and only 40 per cent of the ventures can manage to survive in the market. There are a lot of theories as to why so many new ventures fail. One such theory revolves around financial skill. Inadequate business acumen, including poor financial skill undermines entrepreneurial activity. Financial skill is considered to be one of the critical managerial competencies in new venture creation and development.